(untitled) (The Pakistan Development Review, 2001)
The issue of poverty in Pakistan has its significance for sustainable development. Long run development is not possible without protecting the rights of the vulnerable groups and the participation of the entire population in the development process. A notable development in the last decade in Pakistan’s economic scene has been the sharp pick up in the incidence of poverty. It can be attributed to several factor. The real GDP growth fell from 6 percent in the 1980s to 5 percent in the first half of the 1990s and declined further to just over 4 percent in the second half of the decade. The rate of inflation remained in single digits throughout the 1980s but had a rapid increase of 12 percent during the first half of the 1990s. It is significant to note that food prices generally rose more sharply than overall consumer price index. The unemployment rate increased by 2 percent in the 1990s as compared to in the 1980s reflecting the deceleration of labour absorption in the economy in response to the significant decrease in the economic growth during the nineties.